Better visual outcome at 1 year with antivascular endothelial growth factor treatment according to treat‐and‐extend compared with pro re nata in eyes with neovascular age‐related macular degeneration. Issue 5 (3rd December 2018) - Aurell, Sandra; Sjövall, Kersti; Paul, Anna; Morén, Åsa; Granstam, Elisabet
Abstract: Purpose: To evaluate treatment outcome at 12 months in eyes with neovascular age‐related macular degeneration (nAMD) treated with antivascular endothelial growth factor (anti‐VEGF) injections according to either pro re nata (PRN)‐ or treat‐and‐extend (TE)‐regimen in one clinical setting in Sweden. Methods: Data were obtained retrospectively from the Swedish Macula Register, optical coherence tomography‐database and electronic patient charts. The study included 443 eyes; 223 PRN‐ and 220 TE‐treated eyes. Baseline (BL) characteristics and follow‐up data at 6 and 12 months were collected. Statistical regression analysis was performed to evaluate association between treatment strategy and visual outcome at 12 months. Results: Baseline (BL) characteristics were well balanced between cohorts. Visual acuity at 12 months was higher in TE‐cohort 66.5 (13.1) compared to PRN‐cohort 60.1 (17.6) (p = 0.000). Visual improvement at 12 months was +5.2 (11.8) and +1.2 (12.7) letters Early Treatment Diabetic Retinopathy Study (ETDRS) in TE‐ and PRN‐cohorts, respectively (p = 0.002). Number of administered injections at 12 months was 10.2 (2.1) and 6.3 (2.1) in the two cohorts (p = 0.000). Statistical analysis demonstrated a strong association between TE treatment strategy and improvement in visual acuity at 12 months. Conclusion: Eyes treated according to TE had better visual outcome at 12 months. The results indicate that treatment according to proactive TE‐regimen is superior to treatment according to PRN‐regimen in clinical routine care of nAMD.